2006
DOI: 10.2135/cropsci2005.08-0292
|View full text |Cite
|
Sign up to set email alerts
|

Corn Seed Germination and Vigor Following Freezing during Seed Development

Abstract: The potential for an early autumn frost to reduce corn (Zea mays L.) seed quality is a concern for seed producers. This study evaluated the effect of freezing rate, freezing temperature (−6, −11°C) and duration (4, 6 h), ear attachment, and endosperm composition on seed germination and vigor (accelerated aging [AA] and cold test) during seed development and maturation of six corn hybrids in 1998, 1999, and 2000. Severe reductions in seed germination and vigor occurred for the most immature seeds frozen at >400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
(46 reference statements)
0
14
0
1
Order By: Relevance
“…One of the major concerns of hybrid maize seed producers is the potential for early fall frosts to reduce maize seed quality. This is especially the case in the northern US maize belt (Woltz et al, 2006) and the Hexin Corridor of Gansu province in China. Because of the risk of early frosts, seed companies must consider the stage of seed development when making harvesting decisions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the major concerns of hybrid maize seed producers is the potential for early fall frosts to reduce maize seed quality. This is especially the case in the northern US maize belt (Woltz et al, 2006) and the Hexin Corridor of Gansu province in China. Because of the risk of early frosts, seed companies must consider the stage of seed development when making harvesting decisions.…”
Section: Discussionmentioning
confidence: 98%
“…However, germination was not affected when seeds at lower SMC (300 g kg -1 ) were exposed to low temperatures. Woltz et al (2006) reported that seeds would have higher germination and vigor if they were harvested before a freezing event at an immature stage (B400 g kg -1 SMC) than if they were exposed to freezing temperatures. In this study, we found that the four traits of seed vigor were synchronized at the day after pollination.…”
Section: Discussionmentioning
confidence: 99%
“…Because the high protein genotypes had a genetic background partly related to Mo17 we suspected the premature harvest would have had a seed quality effect. However, the seed quality was less affected by premature harvest than it would have been by leaving the corn in the field subject to frost (Woltz et al, 2006). Table I • C) with a greater impact during seed development, while in 2004 both experiments had only 3 stress degree days before pollination (data not shown).…”
Section: Field Experimentsmentioning
confidence: 89%
“…In this study seeds were subjected to an artificial frost when they were immature and, consequently, damage should have been extensive. However, recent studies assign less importance to the characteristics of the endosperm in preventing or reducing the severity of frost damage in corn (Woltz et al, 2006). The embryo and embryo axis should have the most severe symptoms of freezing, when compared to the endosperm, and detection could be difficult.…”
Section: Frost Damagementioning
confidence: 99%